Future and Present Hedonistic Time Perspectives and the Propensity to Take Investment Risks: The Interplay Between Induced and Chronic Time Perspectives - Sekścińska, Katarzyna; Rudzinska-Wojciechowska, Joanna; Maison, Dominika Agnieszka (Frontiers in Psychology, 2018)
Willingness to take risk is one of the most important aspects of personal financial decisions, especially those regarding investments. Recent studies show that one’s perception of time, specifically the individual level of Present Hedonistic and Future Time Perspectives (TPs), influence risky financial choices. This was demonstrated for both, Time Perspective treated as an individual trait and for experimentally induced Time Perspectives. However, on occasion, people might find themselves under the joint influence of both, chronic and situational Time Perspectives and little is known about interactions between them. The paper focuses on the interplay between chronic and induced levels of Future and Present Hedonistic TPs in explaining people’s propensity to take investment risks. An experimental study using a Polish national random-quota sample was conducted. The results showed that situationally induced Future TP lowered the preferred level of portfolio riskiness while situationally induced Present Hedonistic TPs resulted in exactly the opposite effect, and that the higher level of chronic Present Hedonistic TP was linked to higher investment risk preferences. The role of the chronic Present Hedonistic TP was moderated by the situationally induced Future (approaching significance) and Present Hedonistic TPs. The induction of these TPs resulted in reduction of the propensity to take investment risks. The study adds to the literature on psychological factors influencing the propensity to take financial risk. The results are also important for researchers who experimentally manipulate variables that might be also considered as chronic traits. They indicate that whether the manipulation is congruent with one’s natural tendencies may have a differential impact on subsequent measures.